An unusual case of cavitary lung lesion in catheter related blood stream infection - Koley, Himadri; Saini, Sandeep; Cheluvaiah, Chandrashekar; Dhoot, Dipesh K.; Sindhu, Devada (International Journal of Research in Medical Sciences, 2023)
Cavitary lung lesions are commonly caused by Staphylococcus aureus, Klebsiella pneumoniae. Pseudomonas rarely causes such lesion. Here we report a case of cavitary pneumonia due to pseudomonas aeruginosa in the setting of catheter related blood stream infection in a 25-year-old male with crescentic IgA nephropathy who was on immunosuppressive medication.